Authentic Happiness Pada Guru Honorer (International Forum of Researchers and Lecturers, 2024)
Authentic happiness is happiness that describes the overall goal of positive psychology efforts which includes positive feelings (such as comfort) and positive activities that do not consist of negative emotions at all (such as absorption and involvement). Authentic happiness for honorary teachers is very important to achieve because it is an effort to create enthusiasm, a sense of joy, love for happiness, and prosperity in life. This research aims to determine the picture of authentic happiness in honorary teachers. This research uses a qualitative phenomenological approach with interview and observation methods. This research was conducted on 7 informants. From the research conducted, it was found that a picture of authentic happiness in honorary teachers was obtained in different ways. Most honorary teachers find their happiness by establishing positive relationships with the school environment and outside the school, accepting themselves in the past and present, and maintaining the habit of being grateful and remaining optimistic for the future.